Pengaruh Kebijakan Pemerintah dalam Peningkatan Keunggulan Komparatif dan Kompetitif Usahatani Pala Rakyat di Provinsi Maluku, Indonesia - Simanjorang, Tienni Mariana; Irham; Waluyati, Lestari Rahayu; Mulyo, Jangkung Handoyo (Analisis Kebijakan Pertanian, 2025)
The smallholders nutmeg farming plays an important role in Maluku Province, especially Central Maluku Regency as the largest nutmeg producer. In this connection, the role of government in increasing the competitiveness of nutmeg farming is badly needed. This study aims: (1) to determine the characteristics of smallholder nutmeg farming in Maluku Province, (2) to determine the level of comparative and competitive advantage of nutmeg farming, and (3) to determine the role of government in increasing the comparative and competitive advantage of nutmeg farming. 180 farmers were interviewed in three sub-districts in Central Maluku Regency. Policy Analysis Matrix (PAM) is used to measure the level of competitiveness and multiple regression analysis is employed to determine the effect of government policies on the competitiveness of smallholder nutmeg farming. The results showed that the level of comparative and competitive advantage of smallholder nutmeg farming in Maluku province was high. The results of the analysis also show that government policies have a significant impact, especially on increasing competitive advantage. This indicates the need for government program related to competitiveness of the smallholders’ nutmeg farming, especially in improving the price of seeds and mace prices by taking into account the location of the nutmeg commodity.